Online Education Research in the Islamic World: A Bibliometric Systematic ‎Review - Hasan Mahmoud Abu Hasna; Fatima Saleh Al Blooshi (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This research explores the online education studies in the Islamic world through a comprehensive systematic review of the literature, employing the PRISMA framework. It also investigates trends in yearly distribution, geographical distribution, leading authors, and prominent educational institutions in the field, as well as the perceived benefits and challenges of online learning during the COVID-19 pandemic. Data was obtained from the Scopus database. Methodology: Data was systematically obtained from the included studies using a standardized model. This included information about authors, publication year, study design, methodologies, key findings, and conclusions related to online education in Islamic education. The extracted data were then analyzed to identify themes, trends, and common gaps in literature. The current research identified 125 initial records, screened 114, and included 32 studies in the final review. During the full-text review, articles were assessed for relevance to the role of online education in the Islamic world. Studies not specifically addressing this topic or failing to meet quality standards were excluded. Ultimately, 32 studies were included in the final review. Search Strategy: The research employed the following search strategy using the Scopus database: TITLE-ABS-KEY (Islamic AND educational AND online AND education) AND PUBYEAR > 2012 AND PUBYEAR < 2024 AND (LIMIT-TO (LANGUAGE, "English")) AND (LIMIT-TO (DOCTYPE, "re") OR LIMIT-TO (DOCTYPE, "cp") OR LIMIT-TO (DOCTYPE, "ar")). The search was limited to English-language publications, focusing on review articles, conference papers, and journal articles. Framework Used in the Study (PRISMA Framework): The PRISMA flowchart was used to document the selection process, providing a transparent overview of the number of records identified, included, and excluded at each stage of the review. The final dataset consisted of 32 studies, which formed the basis for the comprehensive analysis presented in this review. By adhering to PRISMA guidelines and utilizing the Scopus database, this review followed a systematic and rigorous approach to gather available evidence regarding the role of online education in the Islamic world. Results: The main findings revealed that the peak of research activity occurred in 2023, with significant contributions from Indonesia and Malaysia. Effective technological tools such as Moodle and Google Classroom were identified, along with the importance of ethical guidelines and professional development for teachers. Conclusions: This review highlighted the significant impact of online learning on teaching methods, providing insights into future research and practice in education within the Islamic world, emphasizing the need for continuous adaptation and innovation in educational strategies. The review emphasized the need for ongoing professional development and ethical guidelines to ensure the responsible use of these technologies. The insights gained from this review offer a foundation for future research and practice in integrating online education in the Islamic world, aiming to enhance educational practices and outcomes in the post-pandemic world.